"It's a kind of double-edged sword": exploring the social media-related experiences of adults with visible differences using photo-elicitation interviews. - Ella Guest; Wylde Roberts-Mills; Anna Zarola; Amy Slater (PLoS ONE)
Objectives Visible differences are associated with experiences of stigma, discrimination, anxiety, and social isolation. Social media provides a space to connect with others with the same condition, gain information and support, raise awareness, and challenge misconceptions. This study aimed to explore the social media experiences of adults with visible differences. Methods An inductive qualitative design was employed, using online participant-driven, semi-structured photo-elicitation interviews with seventeen adults (14 female, 2 male, 1 non-binary) with a range of visible differences. Participants selected screenshots of social media posts which were used to guide the interviews. Reflexive thematic analysis was used to analyse the data and identify common themes, using NVivo 14 software. Findings Three over-arching themes were generated: (1) Filtered realities: feeling self-conscious in a landscape of appearance ideals; (2) Developing my online self: a pathway to accepting my offline self; and (3) A place to belong: building visible difference communities online. Discussion Adults with visible differences face similar appearance pressures on social media to the general population; however, the visible nature of their condition makes it more difficult for them to adhere to these norms. However, some had learned to use social media in a positive way to develop confidence and it provided a space to connect and gain advice from experts by experience. Participants felt that social media was a platform to increase representation of visible differences and normalise conditions; yet they acknowledged that balancing authenticity with content that received the most favourable engagement was a challenge.